Structural & functional studies of L-PGDS and SMPDL3A enzymes in lipid signaling family - Lim, Sing Mei (2016)
Enzymes are indispensable in maintaining the biological system. They metabolize complex molecules to supply nutrients, to produce energy, to regulate transcription of gene expression, and to control the concentration of effective signaling molecules in a cell, thus maintaining the homeostasis of biological system. This thesis summarizes the study of the structure and function of two enzymes in lipid signaling family using integrative application of X-ray crystallography, solution NMR spectroscopy, light scattering, ITC and thermal shift assay. Lipocalin prostaglandin D synthase (L-PGDS) is a tissue specific prostaglandin D2 producing enzyme with a lipocalin fold. Apart from its enzymatic role, it is known to act as a lipophilic ligand carrier. Crystal structure of human L-PGDS and substrate analog altogether with NMR spectroscopy experiments revealed binding sites for substrate catalysis and entry. NMR titration experiments with membrane mimetic showed that L-PGDS has intrinsic membrane binding affinity depending on the ligand bound. These results allowed a model of substrate catalysis and product egression to be proposed, hence, converging the enzymatic and transporter role that has been reported in literature previously. Since prostaglandin D2 is a pivotal inflammatory signaling molecule, molecular understanding of L-PGDS is important to facilitate future regulation of the prostaglandin isomerase. The dynamics of substrate-product exchange may guide future design of this lipophilic carrier as vehicle for drug delivery. The second enzyme, human acid sphingomyelinase like 3a (SMPDL3a), belongs to a metallophosphodiesterase family and shares close sequence identity with human acid sphingomyelinase (aSMase). SMPDL3a’s structure is reported for the first time revealing its binuclear catalytic core site bound with Zn metal. Even though it was presumed to be part of the lipid hydrolase family, enzymatic assays showed that it metabolizes nucleotides and modified nucleotides like CDP-choline, CDP-ethanolamine and ADP-ribose. Subsequently, CDP-choline soaked crystal revealed 5’ cytidine monophosphate (CMP) ligand bound in the catalytic site due to spontaneous catalysis. Its α-phosphate forms key interactions with histidine residues in the binuclear center. Based on this CMP-enzyme structure, general catalytic mechanism of aSMase family can be proposed. Besides, SMPDL3a also serves as a template for aSMase catalytic domain homology modeling. Further study on enzymes in the acid sphingomyelinase family can now be guided by the newly available structural information.